Framework for the Application of System Thinking untuk Monitoring Inventory Barang pada Toko Koperasi Bina Mulia Cibitung - Muhammad khaerudin; Andy Achmad Hendharsetiawan; Suryani, Rani (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
The Bina Mulia cooperative store sells school books and stationery. Information about the inventory of goods in the store is recorded, requests for goods, processes goods out and reports are made without a computerized system, resulting in errors in searching for the required data. The best solution to solve existing problems is to create a web-based inventory system. Constructed information system with FAST method and system design with UML. With the existence of an information system that is made it can make it easier to get information related to transactions. On the main web page there is graphic info that shows the stock of goods making iteasier to monitor available goods. Printing reports on goods received and issued at the store can be done easily by accessing a menu that is easy to find on the system display.